Coronavirus disease 2019: Repeated immersion of chlorine-containing disinfectants has adverse effects on goggles - Zhang, Xiao-bo; Wei, Yu-ling; Zhao, Gang; He, Mei; Sun, Jun; Zeng, Wen (Frontiers in Public Health, 2023)
Introduction During COVID-19, some front-line personnel experienced varying degrees of eye discomfort due to the use of goggles repeatedly disinfected with chlorine-containing disinfectant. Methods The eye damage information of 276 front-line personnel who used goggles in a hospital from October 1, 2021, to December 1, 2021, was collected by filling out a questionnaire. To study the effect of chlorinated disinfectants on goggles, we immersed the goggles in the same volume of water and chlorinated disinfectant buckets. We tested the light transmittance, color and texture, and airtightness of the goggles at different times (1, 3, 12, 24, 36, 48, 60, 72, 96, 120, 144, 168, 192, 216, 240, and 268 h). In addition, we detected where chlorinated disinfectant remained in the goggles by using disinfectant concentration test paper. Results 60 (21.82%) people experienced dry eyes, stinging pain, photophobia and tearing, conjunctival congestion, eyelid redness, and swelling. After treatment or rest, the patient's ocular symptoms were significantly relieved within 3 days. With the extension of disinfection time, the light transmission of the lenses gradually decreased, and the light transmission reduced when immersion occurred at 216 h. After 72 h of disinfection, the color of the goggle frame began to change to light yellow, the texture gradually became hard and brittle, and the color became significantly darker at 268 h of disinfection. The airtightness of the goggles began to decrease after 168 h of disinfection, the airtightness decreased substantially at 268 h, and the shape changed significantly. In addition, the concentration test paper results show that the disinfection solution mainly resides in the goggle frame seam and goggles' elastic bands' bundle. Conclusions Repeated chlorine disinfectant disinfection will reduce the effectiveness of goggles protection and damage front-line personnel's eye health.